Group portrait of YWCA officers - Unknown:::Creator::::::::::::
Group portrait of the YWCA officers (left to right): Mrs. Robert L. Wilson, president, Mrs. Walter Svenson, treasurer, Mrs. John Goldsborough, secretary, Mrs. P.L. Zimmerman, second vice president, Mrs. Earl Dailey, first vice president.